2012
DOI: 10.1038/bjc.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of membrane complement inhibitors CD55 and CD59 by siRNA sensitises uterine serous carcinoma overexpressing Her2/neu to complement and antibody-dependent cell cytotoxicity in vitro: implications for trastuzumab-based immunotherapy

Abstract: Background:We evaluated the expression of CD46, CD55 and CD59 membrane-bound complement-regulatory proteins (mCRPs) in primary uterine serous carcinoma (USC) and the ability of small interfering RNA (siRNA) against these mCRPs to sensitise USC to complement-dependent cytotoxicity (CDC) and antibody (trastuzumab)-dependent cellular cytotoxicity (ADCC) in vitro.Methods:Membrane-bound complement-regulatory proteins expression was evaluated using real-time PCR (RT–PCR) and flow cytometry, whereas Her2/neu expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 32 publications
1
28
0
1
Order By: Relevance
“…Because immune cell activities are often responses to external stimulation by other cell types, cocultures of cancer cells and immune cells are frequently used to assay specific immune cell activities, including changes in cytokine production and release [196][197][198], anti-cancer cytotoxic activities [199][200][201], and immune cell maturation and differentiation [202,203]. Interestingly, the communication between cancer cells and immune cells appears to be bidirectional, with immune cells also modulating cancer cell characteristics such as migratory potentials [204,205] and chemokine production [206].…”
Section: Co-cultures With Immune Cellsmentioning
confidence: 98%
“…Because immune cell activities are often responses to external stimulation by other cell types, cocultures of cancer cells and immune cells are frequently used to assay specific immune cell activities, including changes in cytokine production and release [196][197][198], anti-cancer cytotoxic activities [199][200][201], and immune cell maturation and differentiation [202,203]. Interestingly, the communication between cancer cells and immune cells appears to be bidirectional, with immune cells also modulating cancer cell characteristics such as migratory potentials [204,205] and chemokine production [206].…”
Section: Co-cultures With Immune Cellsmentioning
confidence: 98%
“…These strategies include blockade of the activity of the regulators, downregulation of their expression, or their removal from the cell surface (Brasoveanu et al 1996 ; Ajona et al 2007 ; Di Gaetano et al 2001 ; Andoh et al 2002 ; Blok et al 2003 ; Nagajothi et al 2004 ; Terui et al 2006 ; Shi et al 2009 ; Gao et al 2009 ; Hsu et al 2010 ; Geis et al 2010 ; Bellone et al 2012). However, targeting inhibitory molecules to complement regulators in vivo is technically challenging and may have unwelcome consequences for normal cells.…”
Section: 4 Mechanisms For Adaptation and Control Of Complement Actmentioning
confidence: 99%
“…mCRPs upregulation lead to inactivation of C4b/C3b, dissociation of C3/C5-convertases and prevention of membrane-attack complex assembly (107). Recently, our research group has shown that USC overexpress CD46, 55 and 59 relative to normal endometrial cells; knockdown via siRNAs of CD55 and CD59 but not CD46 significantly sensitized USC to CDC (from 6.8 to 11%) and ADCC (from 48 to >60%) (108). Inhibition of mCRPs on type II endometrial cancers harboring c-erbB2 gene amplification may prove to be a useful strategy to improve the response of these aggressive tumors to trastuzumab-mediated CDC and ADCC (108).…”
Section: Immunotherapymentioning
confidence: 99%